2020
DOI: 10.12669/pjms.36.3.1683
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the clinical application of mixed reality technology leading micro-invasive intervertebral foramen puncture location and blind puncture location

Abstract: Objective: To discuss the function of mixed reality (MR) technology in guiding location of intervertebral foramen microscopic puncture and analyze its feasibility and clinical application value. Methods: Sixty patients with lumbar intervertebral disc who were treated between January 2017 to October 2017 were chosen, and classified into navigation group (30 cases) and traditional control (30 cases) according to random number table. Intervertebral foramen microscopic operation was conducted for both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, in orthopaedic trauma surgery, AR use was not already validated [9]. As shown in numerous experimental studies [24,[44][45][46][47][48][49][50], such as the one conducted by Cho et al [51], AR's potential practical applications appear countless. Some of these are still under development, while others have been proven successful in animals and still need to be redesigned for human application.…”
Section: Discussionmentioning
confidence: 99%
“…However, in orthopaedic trauma surgery, AR use was not already validated [9]. As shown in numerous experimental studies [24,[44][45][46][47][48][49][50], such as the one conducted by Cho et al [51], AR's potential practical applications appear countless. Some of these are still under development, while others have been proven successful in animals and still need to be redesigned for human application.…”
Section: Discussionmentioning
confidence: 99%
“…Within orthopedic surgery, MR has mostly been used in spinal procedures, such as lumbar pedicle screw implantation, operational treatment of lumbar intervertebral disc herniation, and percutaneous kyphoplasty [31][32][33]. Several comparative studies report reduced bleeding and radiation exposure, shorter operating times, improved accuracy of screw placement, higher success rates, and improved pain and functionality scores when MR was compared to traditional x-ray guidance [31][32][33]. These results were attributed to improved anatomical understanding, resulting in smaller surgical trauma and a clearer incision site [32].…”
Section: Intraoperative and Interventional Guidancementioning
confidence: 99%
“…Several comparative studies report reduced bleeding and radiation exposure, shorter operating times, improved accuracy of screw placement, higher success rates, and improved pain and functionality scores when MR was compared to traditional x-ray guidance [31][32][33]. These results were attributed to improved anatomical understanding, resulting in smaller surgical trauma and a clearer incision site [32]. Reported disadvantages to MR include higher requirements for preoperative CT imaging, which might restrict its use to more specialized centers [31][32][33].…”
Section: Intraoperative and Interventional Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were performed in neurosurgery, 33 general surgery 22 and orthopaedic surgery. 14 Figure 6 shows studies of different designs grouped by authors' surgical specialities. 14 studies in orthopaedic surgery were identified, of which there were five RCTs, three prospective cohort studies, two case series and two cases reports (Figure 6).…”
Section: Literature Search Summarymentioning
confidence: 99%